The influence of body size on the pharmacodynamic and pharmacokinetic response to clopidogrel and prasugrel: A retrospective analysis of the FEATHER study - Jakubowski, Joseph A.; Angiolillo, Dominick J.; Zhou, Chunmei; Small, David S.; Moser, Brian A.; ten Berg, Jurrien M.; Brown, Patricia B.; James, Stefan; Winters, Kenneth J.; Erlinge, David (Thrombosis research, 2014)
Patients treated with clopidogrel who have higher body size exhibit greater platelet reactivity than patients with lower body size. In a retrospective analysis of the FEATHER trial, we examined the relationship between platelet response to thienopyridines clopidogrel 75mg (Clop-75), prasugrel 5mg (Pras-5), and prasugrel 10mg (Pras-10) using 3 body size indices: body weight (BW), body mass index (BMI), and body surface area (BSA). Relationships were assessed as continuous variables and as 4 incremental body size groups. Aspirin-treated patients with stable coronary artery disease (N=72) and a BW range of 45-134kg received Clop-75, Pras-5, and Pras-10 in a 3-period, blinded, cross-over study. Platelet assays included maximum platelet aggregation (MPA) to 20μM ADP by light transmission aggregometry, VerifyNow-P2Y12 reaction units (PRU), and vasodilator-associated stimulated phosphoprotein (VASP) phosphorylation platelet reactivity index (PRI). Exposure to active metabolites (AMs) was also assessed. Body size was a determinant of AM exposure and residual platelet reactivity regardless of type and dose of thienopyridine. BW and BSA demonstrated marginally stronger correlations with platelet reactivity; VASP-PRI demonstrated a stronger correlation with the body size than the other tests. Correlation coefficients ranged from a high of 0.64 (BW vs. PRI on Pras-5) to a low of 0.34 (BMI vs. MPA on Pras-10), but all were statistically significant (p<0.01). Using a comprehensive selection of body size indices, AM exposures, platelet function tests, and thienopyridine doses, we demonstrated a consistent inverse relationship between body size and response to clopidogrel and prasugrel.